Technology-Enhanced Civic Education: A Systematic Literature Review of Digital Learning Systems and Civic Competencies - Rosyad, Ali Miftakhu (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
Technology transforms civic education delivery and outcomes in higher education institutions worldwide. This systematic review addresses a critical gap by synthesizing empirical evidence on how specific digital learning systems support civic competency development, examining which technological features and pedagogical integration strategies effectively cultivate democratic citizenship capabilities. Following PRISMA guidelines, we analyzed 63 peer-reviewed articles published between 2014-2024 from Scopus, Web of Science, ERIC, and IEEE Xplore databases. Results show that technology-enhanced approaches combining interactive systems with structured pedagogy produce moderate to large effects (d=0.51-1.18) on civic competencies, while technology-as-content-delivery shows minimal effects (d=0.14-0.38). However, 79% of studies measure outcomes within one month post-intervention using self-report instruments, limiting conclusions about sustained behavioral change. Four categories of digital learning systems emerged: learning management systems, specialized civic platforms, immersive technologies, and social networking tools. Substantial gaps exist in longitudinal behavioral research, implementation science studies, and comparative system effectiveness analyses. Critical Gap: No prior systematic review has explicitly synthesized empirical evidence on which digital learning systems and pedagogical integration strategies most effectively develop all four civic competency dimensions (cognitive, participatory, affective, and behavioral) in higher education globally, including in developing and Asian contexts where this urgency is greatest. Novelty: This study provides the first PRISMA-guided, cross-dimensional synthesis demonstrating that pedagogical integration quality—not technological sophistication—is the primary predictor of civic learning outcomes, offering an evidence-based framework transferable across diverse institutional and cultural contexts worldwide.